Nilai Kejujuran dalam Pendidikan Karakter : Studi Hadis Bukhari No. 5629 - Sahroh, Alfi; Rizkiyah, Nayla Na’imatur (Lembaga Rumah Indonesia, 2021)
Honesty is one of the basic forms in shaping a person's character, both from the family, school, and community environment. However, as time went on, the value of honesty began to erode. Corruption, cheating, plagiarism are one form of the erosion of the value of honesty. This paper will discuss the value of honesty by referring to the Hadith Bukhari no. 5629. This writing uses the ma'anil hadith method, examining the hadiths from takhrij hadiths, criticism of sanad, rawi, matan and understanding the meaning. The result of this writing is that Bukhari hadith no. 5629 regarding honesty is a valid hadith, both in terms of sanad, rawi, and mind. Understanding the ma'na with the language approach has also explained the essence of the ma'na contained in the hadith. The results of the implementation of the hadith show that the value of honesty in character education is formed from habits. Therefore, always speaking and being honest will lead to harmony and social order. Meanwhile, the habit of lying will lead to social conflict, both from real life and in cyberspace